Atypical Neuropsychiatric Presentation in a Patient Expecting Liver Transplantation - Laury Chamelian; Austin Pereira; Kiran Grant; Catherine Maurice (Case Reports in Transplantation)
Patients presenting with acute or chronic hepatopathy can develop altered mental status with psychomotor slowing, most commonly indicating encephalopathy. We present the case of a 56-year-old patient who developed subacute atypical neuropsychiatric symptoms including cognitive and behavioural disorganization, manic-like state, and lateralized parkinsonian syndrome. The sequence of events, complete work-up, and detailed neuropsychiatric examination were not compatible with hepatic encephalopathy or delirium; therefore we extended our differential diagnosis and suggested the pathophysiological process described below.